Biliary Events and GLP-1 Receptor Agonist Therapy in Adolescents and Young Adults - Josélio Rodrigues de Oliveira Filho; Lena Papadakis; Reagan A. Collins; Ghadeer N. Shnawa; Cornelia L. Griggs (JAMA Pediatrics, 2026)
This cohort study explores biliary outcomes associated with use of glucagon-like peptide-1 receptor agonists in youths aged 12 to 21 years with overweight or obesity diagnosis.